Fatty liver on computed tomography scan on admission is a risk factor for severe coronavirus disease. Issue 2 (February 2022) - Okuhama, Ayako; Hotta, Masatoshi; Ishikane, Masahiro; Kawashima, Akira; Miyazato, Yusuke; Terada, Mari; Yamada, Gen; Kanda, Kohei; Inada, Makoto; Sato, Lubna; Sato, Mitsuhiro; Akiyama, Yutaro; et al.
Abstract: Objectives: To alleviate the overflow of coronavirus disease 2019 (COVID-19) patients in hospitals, less invasive and simple criteria are required to triage the patients. We evaluated the relationship between COVID-19 severity and fatty liver on plain computed tomography (CT) scan performed on admission. Methods: In this retrospective cohort study, we considered all COVID-19 patients at a large tertiary care hospital between January 31 and August 31, 2020. COVID-19 severity was categorized into severe (moderate and severe) and non-severe (asymptomatic and mild) groups, based on the Japanese National COVID-19 guidelines. Fatty liver was detected on plain CT scan. Multivariate logistic regression analysis was performed to evaluate factors associated with severe COVID-19. Results: Of 222 patients (median age: 52 years), 3.2%, 58.1%, 20.7%, and 18.0% presented with asymptomatic, mild, moderate, and severe COVID-19, respectively. Although 59.9% had no fatty liver on plain CT, mild, moderate, and severe fatty liver occurred in 13.1%, 18.9%, and 8.1%, respectively. Age and presence of fatty liver were significantly associated with severe COVID-19. Conclusion: Our study showed that fatty liver on plain CT scan on admission can become a risk factor for severe COVID-19. This finding may help clinicians to easily triage COVID-19 patients.